2016
DOI: 10.1155/2016/4515928
|View full text |Cite
|
Sign up to set email alerts
|

Infant’s DNA Methylation Age at Birth and Epigenetic Aging Accelerators

Abstract: Knowing the biological age of the neonates enables us to evaluate and better understand the health and maturity comprehensively. However, because of dearth of biomarkers, it is difficult to quantify the neonatal biological age. Here we sought to quantify and assess the variability in biological age at birth and to better understand how the aging rates before birth are influenced by exposure in intrauterine period by employing a novel epigenetic biomarker of aging (epigenetic clock). We observed that the methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…In addition to relationships between EAA and growth under energetic constraint, it is also potentially important to understand how concurrent exposure to psychosocial and energetic stressors relates to children's EAA. Multiple studies have shown that individuals experiencing psychosocial adversity prior to adulthood exhibit greater EAA, and children's family environments may play a role in shaping these effects (Brody, Miller, Yu, Beach, & Chen, ; Javed, Chen, Lin, & Liang, ; Jovanovic et al, ; Lawn et al, ; Sumner, Colich, Uddin, Armstrong, & McLaughlin, ; Wolf et al, ). For example, research among African‐American children found that supportive family contexts were protective for children against the effects of racial discrimination on EAA (Brody, Yu, Chen, Beach, & Miller, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to relationships between EAA and growth under energetic constraint, it is also potentially important to understand how concurrent exposure to psychosocial and energetic stressors relates to children's EAA. Multiple studies have shown that individuals experiencing psychosocial adversity prior to adulthood exhibit greater EAA, and children's family environments may play a role in shaping these effects (Brody, Miller, Yu, Beach, & Chen, ; Javed, Chen, Lin, & Liang, ; Jovanovic et al, ; Lawn et al, ; Sumner, Colich, Uddin, Armstrong, & McLaughlin, ; Wolf et al, ). For example, research among African‐American children found that supportive family contexts were protective for children against the effects of racial discrimination on EAA (Brody, Yu, Chen, Beach, & Miller, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to relationships between EAA and growth under energetic constraint, it is also potentially important to understand how concurrent exposure to psychosocial and energetic stressors relates to children's EAA. Multiple studies have shown that individuals experiencing psychosocial adversity prior to adulthood exhibit greater EAA, and children's family environments may play a role in shaping these effects Javed, Chen, Lin, & Liang, 2016;Jovanovic et al, 2017;Lawn et al, 2018;Sumner, Colich, Uddin, Armstrong, & McLaughlin, 2019;Wolf et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hannum´s intrinsic age acceleration and Horvath´s extrinsic acceleration were associated positively with former smoking <15 years prior (N=533, ß=0.65±0.33, p=0.05 and ß=0.78±0.3, p=0.03 respectively) and current smoking (<20 cigarettes/day, N=159, ß=2.12±0.52, p<0.001 and ß=1.33±0.58, p=0.02 respectively) (P. A. . Interestingly, infants of smoking mothers, had a higher risk of a positive age acceleration, measured by the difference of the Horvath age estimate and chronological age in cord-blood samples, compared to infants with nonsmoking mothers (N=80, OR= 3.17, 95% CI 1.05-9.56) (Javed et al, 2016).…”
Section: Smokingmentioning
confidence: 99%
“…Contributions (e.g., equipment, logistics, personnel) were made from each of the other participating sites. (Horvath, Gurven, Levine, Trumble, Kaplan, Allayee, Ritz, Chen, Lu, Rickabaugh, Jamieson, Sun, Li, Chen, Quintana-murci, et al, 2016) (Quach, Levine, Tanaka, Lu, Chen, Ferrucci, et al, 2017) (Simpkin et al, 2017) Public DNA methylation dataset (cord blood) N=80 -Horvath -Smoking (Javed, Chen, Lin, & Liang, 2016)…”
Section: Fundingmentioning
confidence: 99%
“…In a separate analysis in this same North Carolina cohort, authors observed an opposite and significant association with neighborhood socioeconomic status (SES) for MEG3 (hypermethylation) [ 41 ]. Finally, a birth cohort study from China [ 42 ] measured DNA methylation at several hundred CpG sites and found that lower maternal SES was associated with older epigenetic age using a novel ‘epigenetic clock’ method. However, repeat element methylation in infants has yet to be examined in relation to socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%